Gênese e classificação de solos em ambientes de planícies da região Nordeste do Brasil. - Silva, Rafael Cipriano da (2012)
Soils formed by sediments in lowland environments have distinct genetic characteristics according to the parent material, which can be basically composed of mineral and organic sediments. The first is formed from the weathering of rocks, and the chemical, physical and mineralogical properties are inherited from the source material. The organic sediments are influenced by the type of vegetation dominant in the landscape, and the addition of organic material under water saturation conditions, that favors the accumulation and thickening of organic sediment layers, which can lead to the genesis of organic soils. This study aimed to evaluate the morphological, physical and chemical properties of six organic soil profiles developed in the coastal region of the States of Ceará, Rio Grande do Norte and Paraíba; besides these attributes and the mineralogical and micromorphological characteristics of four soil profiles from alluvial sediments in the lower course of Acaraú river Basin - CE. The properties evaluated were: color, density, texture, fiber content, degree of decomposition of organic matter, C content, organic matter, N, P and micronutrients, sum of bases, T and V value, humic fractions, degree of water repellency, electrical conductivity, soluble salts, X-ray diffraction, among others. For the Histosols, it was found a positive correlation of the C levels with the soil density, with subsidence, potential acidity, N content and hydrophobicity; as well as influencing the CTC and the content of H+ from the organic acids. The different methods for measuring organic carbon were positively correlated with each other. The C content of humin fraction were higher due to the presence of fibers in this fraction, while the fulvic acid contents were lower compared to the humic acids, indicating increased stability of organic compounds present in these soils. With respect to the soils from alluvial sediments, there were observed high levels of soluble salts, conferring them the saline and sodic characters. This is due to the marine influence and the high water table, besides the presence of weatherable minerals. The micromorphological description showed some aspects related to the soil genesis, such as clay illuviation in depth, the allochthonous origin of the parent material and in situ alteration of the alluvial sediments. The geomorphology was the main factor in the greatest expression of pedogenetic processes in the landscape, and the position where the soils are located is a strong indicator of their environmental fragility.